Opportunities and challenges for collaboration in research and practice in injury prevention across work and other settings - Breslin, F. Curtis; Shannon, H. (Scandinavian Journal of Work, Environment & Health, 2005)
Even though injuries at work and in other settings (homes, roads, etc) commonly involve similar mechanisms, research and prevention are usually specific to each setting. The potential benefits of addressing common features of injury prevention are noted across setting, while some unique features of the work environment are acknowledged. Further integration is recommended using the following approaches: (i) organization of research questions by injury mechanisms and (ii) support of comparative research across settings by funding agencies.
Keywords: injury prevention; opinion; research collaboration; work; workplace